The Difference of Vitamin D and Calcium Levels in Preeclampsia and Normal Pregnancy - Lola Pebrianthy; Nurelilasari Siregar; Ayusdiningsih (Journal of Public Health and Pharmacy, 2021)
Background: The incidence of preeclampsia is still high in the world and in Indonesia. In obstetric care, preeclampsia still a big problem and is a cause of increasing maternal and neonatal mortality and morbidity. This research aimed to discover the difference of vitamin D and calcium level in preeclampsia and normal pregnancy. Methods: The design of this study was cross sectional and conducted in RSUP Dr. M. Djamil Padang and Lubuk Buaya Public Health Center between February 2017 – November 2017. Sample in this research were 25 women with over 20 weeks of pregnancy who are diagnosed with preeclampsia and 25 women with normal pregnancy, gathered using consecutive sampling technic. The vitamin D levels were examined using ELISA and calcium levels using ARSENAZO method. The results were tested for data normality using Shapiro-Wilk, and then the unpaired T-test was performed. Results: The result of this research showed mean vitamin D levels of 417.42 ± 176.02 pg/mL in preeclampsia and 437.16 ± 165.13 pg/mL in normal pregnancy, with p > 0.05. The meancalcium levels were 9.51 ± 1.123 mg/dL and 9.86 ± 0.96 mg/dL in preeclampsia and normal pregnancy, respectively, with p > 0.05. Conclusion: From this research, the author concludes that there were no significant differences of vitamin D in preeclampsia and normal pregnancy, and there were no significant differences of calcium in preeclampsia and normal pregnancy.